Correlations between social-emotional feelings and anterior insula activity are independent from visceral states but influenced by culture - Immordino-Yang, Mary Helen; Yang, Xiao-Fei; Damasio, Hanna (Frontiers in Human Neuroscience, 2014)
The anterior insula (AI) maps visceral states and is active during emotional experiences, a functional confluence that is central to neurobiological accounts of feelings. Yet, it is unclear how AI activity correlates with feelings during social emotions, and whether this correlation may be influenced by culture, as studies correlating real-time AI activity with visceral states and feelings have focused on Western subjects feeling physical pain or basic disgust. Given psychological evidence that social-emotional feelings are cognitively constructed within cultural frames, we asked Chinese and American participants to report their feeling strength to admiration and compassion-inducing narratives during fMRI with simultaneous electrocardiogram recording. Trial-by-trial, cardiac arousal and feeling strength correlated with ventral and dorsal AI activity bilaterally but predicted different variance, suggesting that interoception and social-emotional feeling construction are concurrent but dissociable AI functions. Further, although the variance that correlated with cardiac arousal did not show cultural effects, the variance that correlated with feelings did. Feeling strength was especially associated with ventral AI activity (the autonomic modulatory sector) in the Chinese group but with dorsal AI activity (the visceral-somatosensory/cognitive sector) in an American group not of Asian descent. This cultural group difference held after controlling for posterior insula activity and was replicated. A bi-cultural East-Asian American group showed intermediate results. The findings help elucidate how the AI supports feelings and suggest that previous reports that dorsal AI activation reflects feeling strength are culture related. More broadly, the results suggest that the brain’s ability to construct conscious experiences of social emotion is less closely tied to visceral processes than neurobiological models predict and at least partly open to cultural influence and learning.